Learning preferences transformation in tertiary education - Revathi, Sagadavan; John, Shiney (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The focus of the study is to have a better insight of preferred learning styles of younger generation collectively. Learning preferences of a learner varies due to many elements. Most of the institutions adopt “student centric” as a vow, but at times it become unrealistic with increased number of students. However, it is possible to identify the transformation in learning preferences of the students to cater teaching and learning process more effective. Index of Learning style (ILS) questionnaire is adopted to identify the learning preferences of the students. The data was collected on an online platform using convenience sampling method. This findings of the study suggested that Malaysian students prefer social media as a main platform to get guidance from the instructor. Furthermore, our students are more visual and sequential oriented learners. This study also emphasizes that learning preferences doesn’t change over time but the mode of conduction is expected to change based on the digital world. This study will help academicians and policy makers to serve students better based on their learning preferences and it is expected to improve the teaching and learning process. The study is limited to Malaysian students, future studies can focus on different countries and on different generations.